Multiscale modelling and simulation of viruses. (April 2020) - Marzinek, Jan K; Huber, Roland G; Bond, Peter J
Highlights: Advances in structural biology and integrative modelling yield (near)-atomic resolution structures of complete viruses. Computer simulations can now elucidate the dynamics of multi-million particle viral systems. Simulations uncover key properties of viral capsids, including permeability, dynamics, and drug binding sites. Simplified, coarse-grained models enable study of long-timescale viral phenomena, such as capsid shell assembly. Multiscale simulations of viral envelopes have uncovered molecular basis for flavivirus life cycle and host interactions. Abstract : In recent years, advances in structural biology, integrative modelling, and simulation approaches have allowed us to gain unprecedented insights into viral structure and dynamics. In this article we survey recent studies utilizing this wealth of structural information to build computational models of partial or complete viruses and to elucidate mechanisms of viral function. Additionally, the close interplay of viral pathogens with host factors — such as cellular and intracellular membranes, receptors, antibodies, and other host proteins — makes accurate models of viral interactions and dynamics essential. As viruses continue to pose severe challenges in prevention and treatment, enhancing our mechanistic understanding of viral infection is vital to enable the development of novel therapeutic strategies.